PERAN ENVIRONMENTAL PERFORMANCE TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG MENGIKUTI PROGRAM PROPER PADA TAHUN 2017-2019 DENGAN DETERMINAN GREEN ACCOUNTING - Heni Yusnita, M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this study is to determine the effect of Green Accounting  on Profitability either direct or indirect with environmental performance as an intervening variabel. The population in this study is the manufacturing companies listed in Indonesian Stock Exchange and follow PROPER program for the years of 2017-2019. The samples was conducted by purposive sampling, with the criteria determined then the number of samples is 31 manufacturing companies. To solve the research question, this study uses simple linier regression analysis and path analysis with SPSS 25 The results of this study indicate that: 1) There is a direct effect of green accounting on environmental performance.2) There is a direct effect of environmental performance on profitability.3) There is a direct effect of green accounting on profitability. 4) Green accounting directly through environmental performance has a significant effect on return on assets.